Convective flow of hydromagnetic couple stress fluid with varying heating through vertical channel - Makhalemele, Cynthia; Rundora, Lazarus; Adesanya, Samuel Olumide (Zielona Góra: Uniwersytet Zielonogórski)
This article addresses the impact of magnetic field induction on the buoyancy-induced oscillatory flow of couple stress fluid with varying heating. Modelled equations for the incompressible fluid are coupled and nonlinear due to the inclusion of viscous heating and thermal effect on the fluid density. Approximate solutions are constructed and coded on a symbolic package to ease the computational complexity.
Keywords: induced magnetic field; couple stress; vertical channel; varying heating